Improved sensitivity of CdS nanoparticles by virtue of calcium doping: Promising candidate for monitoring alcohol in exhale human breath. (15th July 2017) - Chakraborty, Sonam; Pal, Mrinal
Abstract: Search for novel materials or functionalization/modification of materials to develop enhance performance is always challenging. We have tried with success to achieve highest sensitivity towards ethanol by virtue of calcium doping in CdS nanoparticles prepared through sonication technique. Phase purity, structure and chemical composition of the prepared samples were characterized by using X-ray diffraction (XRD), UV–vis spectroscopy, photoluminescense spectroscopy (PL), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) and Fourier transfer infrared spectroscopy (FTIR) techniques. Ca-doped CdS nanoparticle based sensors displayed ultrafast sensing behaviour having a transient response time around 1 s. These sensors showed a minimum detection limit of 500 ppb ethanol with a good response of 32%. In addition, sensors were very much selective and a lowering of operating temperature (around 190 °C) has been achieved in comparison to undoped CdS nanoparticles. Enhancement of surface area and modulation of potential barriers due to doping of calcium plays a crucial role for the improvement of sensing properties. Demonstrated results are very promising and can be explored to fabricate breath analyzer having excellent performance for monitoring alcohol. Graphical abstract: Highlights: Facile synthesis of Ca-doped CdS nanoparticles using sonochemical route. Observed 95.9% response towards 100 ppm of ethanol, highest for any CdS nanostructure. Operating temperature reduces significantly from 270 °C to 190 °C by virtue of Ca doping. Sensors exhibit minimum detection limit of 500 ppb with a good response of 32%. Observed good resolution at low ppm level promising for breath analyzer.